CD10 down expression in follicular lymphoma correlates with gastrointestinal lesion involving the stomach and large intestine. Issue 11 (14th October 2016) - Ohnishi, Nobuhiko; Takata, Katsuyoshi; Miyata‐Takata, Tomoko; Sato, Yasuharu; Tari, Akira; Gion, Yuka; Noujima‐Harada, Mai; Taniguchi, Kohei; Tabata, Tetsuya; Nagakita, Keina; Omote, Shizuma; Takahata, Hiroyuki; et al.
Abstract : Follicular lymphoma (FL) shows co‐expression of B‐cell lymphoma 2 (BCL2) and CD10, whereas downexpression of CD10 is occasionally experienced in gastrointestinal (GI) FL with unknown significance. Gastrointestinal FL is a rare variant of FL, and its similarity with mucosa‐associated lymphoid tissue lymphoma was reported. We investigated the clinicopathological and genetic features of CD10 downexpressed (CD10 down ) GI‐FL. The diagnosis of CD10 down FL was carried out with a combination of pathological and molecular analyses. The incidence of CD10 down GI‐FL was shown in 35/172 (20.3%) cases, which was more frequent than nodal FL (3.5%, P < 0.001). The difference was additionally significant between GI‐FL and nodal FL when the analysis was confined to primary GI‐FL (55.2% vs 3.5%, P < 0.001). Compared to CD10 + GI‐FL, CD10 down GI‐FL significantly involved the stomach or large intestine ( P = 0.015), and additionally showed the downexpression of BCL6 ( P < 0.001). The follicular dendritic cell meshwork often showed a duodenal pattern in the CD10 down group ( P = 0.12). Furthermore, a lymphoepithelial lesion was observed in 5/12 (40%) gastric FL cases, which indicated caution in the differentiation of mucosa‐associated lymphoid tissue lymphoma. Molecular analyses were undertaken in seven cases of CD10 down GI‐FL, and an identical clone was found between CD10 down follicles and CD10 + BCL2 + neoplastic follicles. In the diagnosis of cases with CD10 down BCL2 + follicles, careful examination with molecular studies should be carried out. Abstract : Identical clone was detected between CD10‐down expressed follicle and CD10 + BCL2 + follicle.